Methods, measurements, and novel materials for improving depth filtration processes used in drinking water treatment. - Upton, Andrew (Cranfield University, 2021)
Rapid media filtration is used to treat most surface water sources for municipal drinking water supply. This thesis presents results of an investigation into how media filters in Scottish Water, built decades ago to different standards, can meet increasingly stringent water quality requirements. A new method for efficient assessment of filter performance and diagnosis of issues using online data were developed. A recursive partitioning algorithm applied to operationally relevant predictor variables was shown to efficiently and effectively characterise the conditions associated with elevated turbidity over an extended period of operation. Tree models can then be used to communicate a diagnosis in operational terms to aid the efficient management of individual pathogen barriers in a multi-barrier system. Robust rapid filtration requires effective coagulation. An investigation was conducted at a water treatment works (WTW) to understand the influence of zeta potential. The effective zeta potential window was modelled & observed to change with conditions. The online measurement of zeta potential was shown to be useful for process optimisation by providing a quantitative measurement with a mechanistic basis for coagulation conditions. This provides advantages over jar testing which may poorly represent the system under investigation. Pilot and full-scale trials of an alternative expanded aluminosilicate media show that the additional bed expansion achieved by replacing sand with the lower density material can, at comparatively low cost, improve the performance of rapid gravity filters with a common design limitation. The effective application of new finer grade expanded aluminosilicate was shown at pilot and full scale. This thesis presents a suite of efficient solutions to ensure aging 20th century filters robustly meet challenges in 21st century. This is achieved by improving understanding of how and why specific constraints limit the performance of existing RGFs and developing strategic solutions to overcome common limitations to process performance.
Keywords: Coagulation; filtration; media; water treatment; filter; turbidity